2022
DOI: 10.3390/polym14142808
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Review of Self-Healing Mechanism and Formulation Optimization of Polyurea Coating

Abstract: Self-healing polymers are categorized as smart materials that are capable of surface protection and prevention of structural failure. Polyurethane/polyurea, as one of the representative coatings, has also attracted attention for industrial applications. Compared with polyurethane, polyurea coating, with a similar formation process, provides higher tensile strength and requires shorter curing time. In this paper, extrinsic and intrinsic mechanisms are reviewed to address the efficiency of the self-healing proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…30,31 In Singapore, the monthly average maximum temperature of seawater ranges from 28.2 to 31.0 °C, with an average salinity of approximately 35 ppt. 32 Referring to Figure 12, these values suggest that the average potential amount of dissolved oxygen available is about 6 mg −1 , which is sufficient for the polymerization of tung oil. The process of photosynthesis by vegetation can directly influence the concentration of dissolved oxygen.…”
Section: Polymerization Of Tung Oil By Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 In Singapore, the monthly average maximum temperature of seawater ranges from 28.2 to 31.0 °C, with an average salinity of approximately 35 ppt. 32 Referring to Figure 12, these values suggest that the average potential amount of dissolved oxygen available is about 6 mg −1 , which is sufficient for the polymerization of tung oil. The process of photosynthesis by vegetation can directly influence the concentration of dissolved oxygen.…”
Section: Polymerization Of Tung Oil By Oxidationmentioning
confidence: 99%
“…However, it is important to consider that the addition of microcapsules may impact the adhesion strength of the coatings to the substrate. Studies conducted by J. Luo et al, Y. Li et al, and M. Samadzadeh et al have demonstrated that a higher concentration of embedded microcapsules can result in a decrease in the adhesion strength of the coatings. Despite this, the microencapsulation of drying oil has shown excellent self-healing ability and corrosion resistance . Therefore, careful consideration of the microcapsule concentration is necessary to achieve optimal results without compromising the adhesion strength of the coatings.…”
Section: Intrinsic Factors For Polyurea Self-healing Efficiencymentioning
confidence: 99%
“…(a) Extrinsic self‐healing mechanism using microencapsulated healing agents that are released after microcracking has occurred. Source : Reproduced with permission from Luo et al., Polymers, published by MDPI, 2022. (b) Intrinsic self‐healing mechanism utilizing natural cross‐linking bonds that can reconstruct broken bonds resulting from microcracking.…”
Section: Advanced Edible Coating Technologiesmentioning
confidence: 99%
“…PU-based materials described in the literature are mainly obtained from commercial formulations: prepolymeric diamine components (oligomeric polyether diamines—e.g., Jeffamine ® [ 14 , 21 , 22 ] and Versalink ® [ 23 , 24 ]) and prepolymeric isocyanate components (aromatic isocyanates based on polymeric methylene diphenyl diisocyanate—e.g., Desmodur ® [ 25 ], Rubinate ® [ 26 ], or isophorone diisocyanate [ 27 , 28 ]). Commercial bicomponent prepolymeric formulations (macrodiol and polyisocyanate) are reported for PU-based materials (e.g., Vulkollan ® [ 20 , 29 ] and Multrathan ® [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%